1998
DOI: 10.1002/(sici)1096-9861(19980511)394:3<271::aid-cne1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Birth and fate of proliferative cells in the inner nuclear layer of the mature fish retina

Abstract: In teleost fish, unlike other vertebrates, the retina continues to grow throughout the animal's life both by stretching of the mature tissue and by the addition of new cells. Following larval development, new retinal cell birth is known to occur in a rim at the periphery of the mature retina and in the outer nuclear layer (ONL). We have now found that cell birth and proliferation also occurs in the inner nuclear layer (INL) of the mature fish retina. In rainbow trout (Onchoryncus mykiss), proliferative cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
1
5

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(84 citation statements)
references
References 29 publications
8
70
1
5
Order By: Relevance
“…Our results, indicating the existence of dividing cells in the INL in normal adult fish retina, support the hypothesis of the persistence of these quiescent cells with capacity to proliferate in response to specific cues. In uninjured retina, dividing cells in the INL, with similar characteristics to those observed in regeneration, have been seen in juvenile goldfish (Johns 1982;Otteson et al 2001), after the intraocular injection of growth factors in goldfish (Negishi and Shinagawa 1993) and in rainbow trout (Julian et al 1998). A study of deep-sea fish, including chondrichtyes and several species of marine teleost, also mentions proliferating cells in the INL (Fröhlich et al 1995).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Our results, indicating the existence of dividing cells in the INL in normal adult fish retina, support the hypothesis of the persistence of these quiescent cells with capacity to proliferate in response to specific cues. In uninjured retina, dividing cells in the INL, with similar characteristics to those observed in regeneration, have been seen in juvenile goldfish (Johns 1982;Otteson et al 2001), after the intraocular injection of growth factors in goldfish (Negishi and Shinagawa 1993) and in rainbow trout (Julian et al 1998). A study of deep-sea fish, including chondrichtyes and several species of marine teleost, also mentions proliferating cells in the INL (Fröhlich et al 1995).…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, these cells have not been found in normal adults of some species (Johns 1982;Kim et al 1997). It has been suggested that these cells in the INL proliferate very slowly and, therefore, it is difficult to detect them by transient labels of proliferation such as PCNA or pulse labeling with BrdU (Julian et al 1998;Otteson et al 2001). In the present study, we observed cell proliferation in the INL in adult fish with normal growth rate, by anti-PCNA immunostaining.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations